Modified atmosphere and active packaging technologies - Arvanitoyannis, Ioannis S. (Contemporary food engineering, 2012)
"While other packaging books focus on individual types of packaging, this volume takes an applied engineering approach by matching packaging types to specific food types. The material provides unique insight into Modified/Controlled Atmosphere Packaging/Storage (MAP/CAS) and Active Packaging (AP). Depending on the kind of food, packaging material and the corresponding technique employed can both vary considerably. In appreciation of consumer focus on shelf life and safety, the book addresses a range of aseptic, smart, and modified atmosphere packaging. With the increased expense of active packaging, this resource will help product developers make cost-effective decisions early in product development"--Resumé vydavatele